HOSPITAL SCHOOLS IN FOREIGN COUNTRIES AND THEIR MAIN PURPOSES AND TASKS (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article examines the organizational and pedagogical foundations of hospital schools in foreign countries, as well as their main purposes and functional tasks in ensuring continuity of education for children undergoing long-term medical treatment. The study analyzes international approaches to the establishment of hospital-based educational environments and highlights the role of hospital schools in protecting the child’s right to education, reducing academic interruption, and supporting psychological well-being during illness. Particular attention is given to the integration of medical, pedagogical, and psychosocial support within hospital education systems operating in countries such as the United Kingdom, Germany, the United States, and other developed educational contexts. The article emphasizes that hospital schools perform not only instructional functions, but also developmental, adaptive, rehabilitative, and socializing roles. Their activity is aimed at preserving students’ motivation for learning, facilitating reintegration into mainstream schooling, and creating individualized educational trajectories based on health conditions and treatment regimes. The paper argues that the foreign experience of hospital schools is of considerable scientific and practical value for improving inclusive and medical-pedagogical support systems in modern education.
Keywords: Hospital schools, hospital pedagogy, continuity of education, children with medical needs, inclusive education, individualized instruction, psychosocial support, educational rehabilitation.